Susceptibilities of Mycoplasma hominis and Ureaplasma urealyticum to two new quinolones, sparfloxacin and WIN 57273. - Kenny, G E (1991)
Mycoplasma hominis was highly susceptible to two new quinolones, with MICs for 90% of isolates tested of 0.004 micrograms/ml for WIN 57273 and 0.063 micrograms/ml for sparfloxacin, which were activities much greater than the 1 microgram/ml found for ofloxacin and tetracycline. Although Ureaplasma urealyticum was less susceptible, the MICs for 90% of isolates tested of 0.25 micrograms/ml for WIN 57273 and 0.5 micrograms/ml for sparfloxacin were four- to eightfold greater than those found for ofloxacin (2 micrograms/ml) and tetracycline (2 micrograms/ml). The finding that U. urealyticum and M. hominis are more susceptible to WIN 57273 and sparfloxacin than they are to other quinolones suggests that these quinolones may be therapeutically useful.